Can potato fiber efficiently substitute xanthan gum in modulating chemical properties of tomato products?. (April 2020) - Diantom, Agoura; Boukid, Fatma; Carini, Eleonora; Curti, Elena; Vittadini, Elena
Abstract: In the frame of clean labelling, potato fiber (F) was tested as a potential texturizing agent to substitute xanthan (X) in the tomato industry. For this purpose, a physico-chemical evaluation was performed on three different tomato products [tomato pulp (TP), double (DC) and triple tomato concentrate (TC)] that were processed under different thermal treatments (cold and hot) and added with different levels (1, 1.5 and 2% (g ingredient/100 g tomato product) of texturing agents (F and X). For physical features, a higher redness was obtained at 2% of F in DC and TC, while TP color remained unvaried. Furthermore, F showed a stronger effect on apparent viscosity than X in the case of TP. Concerning chemical features, moisture content, water activity and pH significantly varied among samples, but no clear trend was observed as a function of amount/type of additive. At a molecular level, F reduced proton molecular mobility, in contrast with X. Summarizing, F can be considered a potential "clean label" substitute for X in tomato-based products. Graphical abstract: Image 1 Highlights: Potato fiber was tested as a clean label ingredient in different tomato products. Potato fiber performance was compared to xanthan by multivariate statistics. Potato fiber showed a stronger effect on apparent viscosity than xanthan. Potato fiber reduced proton molecular mobility, in contrast with xanthan.